2001
DOI: 10.1083/jcb.152.6.1307
|View full text |Cite
|
Sign up to set email alerts
|

Importin β–Mediated Nuclear Import of Fibroblast Growth Factor Receptor

Abstract: Although growth factor receptors are generally thought to carry out their role in signal transduction at the cell surface, many of these transmembrane proteins translocate to the nucleus after ligand stimulation. Here, we show that the nuclear translocation of fibroblast growth factor receptor (FGFR)1 occurs via a mechanism distinct from classical nuclear import but dependent on importin β, a component of multiple nuclear import pathways. Furthermore, we show that nuclear FGFR1 induces c-Jun and is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
228
1
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(252 citation statements)
references
References 24 publications
16
228
1
7
Order By: Relevance
“…Furthermore, nuclear import of FGFR is associated with proliferation (Reilly and Maher, 2001), which is in line with the observation that nuclear FGFR enhances c-jun expression (Reilly and Maher, 2001). Also suggested by accumulating evidences is that nuclear FGFR mediates cAMP-activated expression of neurofilament-L and, thus, is important for cAMP-induced differentiation of neuronal progenitor cells into neurons (Stachowiak et al, 2003).…”
Section: Linking Nuclear Egfr To Pathways That Are Important For Tumosupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, nuclear import of FGFR is associated with proliferation (Reilly and Maher, 2001), which is in line with the observation that nuclear FGFR enhances c-jun expression (Reilly and Maher, 2001). Also suggested by accumulating evidences is that nuclear FGFR mediates cAMP-activated expression of neurofilament-L and, thus, is important for cAMP-induced differentiation of neuronal progenitor cells into neurons (Stachowiak et al, 2003).…”
Section: Linking Nuclear Egfr To Pathways That Are Important For Tumosupporting
confidence: 70%
“…Nevertheless, it is becoming clear that several cellsurface receptors are capable of interacting with nuclear transport receptors, importins a/b and exportins, and thus enter and exit the cell nucleus, respectively (Reilly and Maher, 2001;Giri et al, 2005). Association with importin b1 is important for nuclear import of HER-2 and FGFR (Reilly and Maher, 2001;Giri et al, 2005) whereas EGFR has been shown to interacts with both importin b1 and importin a (Dittmann et al, 2005a;. Blockage of RanGDP and importin b1 by dominant-negative mutant and siRNA, respectively, also inhibits nuclear transport of HER-2, suggesting that NPC is involved in the process (Giri et al, 2005).…”
Section: Potential Mechanisms For Nuclear-cytoplasmic Transport Of Cementioning
confidence: 99%
“…In the nuclear pathway, an atypical transmembrane domain in FGFR1 allows newly translated immobile receptor to be released from the pre‐Golgi membrane into cytosol generating a highly mobile protein in a process that involves proteasomes and is facilitated by the FGF‐2 ligand, and ribosomal S6 kinase (Dunham‐Ems et al, 2006, 2009). The nuclear transport of FGFR1 is mediated by importin‐β (Reilly and Maher, 2001). The nuclear accumulation of the hypoglycosylated nuclear form of FGFR1 (nFGFR1) is stimulated by a variety of developmental signals, including various growth factors (i.e., EGF, NGF, BDNF, BMP), vitamins D and retinoids, hormones, and neurotransmitters, calcium, cyclic AMP, and is inhibited by cell contact receptors.…”
Section: Constitutive Plasma Membrane and Regulated Nuclear Targetingmentioning
confidence: 99%
“…The reported tyrosine kinase receptors include four members of ErbB family [11][12][13][14][15] and other tyrosine kinase receptors like VEGF receptor [16], FGF receptor [17,18] and NGF receptor [19]. However, the four members of ErbB family were translocated in the nucleus in different form.…”
Section: Introductionmentioning
confidence: 99%